It happened on the lake [large type] - Jackson, Lisa (Center Point Large Print, 2025)
"The huge Victorian house on Lake Twilight belongs to Harper Reed Prescott, as does the private island on which it sits. Harper wants little to do with either. Twenty years ago, Harper's grandmother died suspiciously while in her care, on the same night that Harper's boyfriend disappeared. His body was never found, and no charges were filed. But the rumors haven't faded. There have been other deaths, other accidents. All revolving around Harper and her family. Now Harper's marriage is over, her college-age daughter is estranged, and Harper just wants to sell the property and make a fresh start. Except returning to the lake has stirred everything up again. Whispers. Memories. And the persistent feeling that, as she gazes out at the houses across the water, she's being watched in turn. The whole town has always thought Harper has something to hide, and they're right. But she might have even more to fear ..."--